2018
DOI: 10.1186/s12906-018-2203-z
|View full text |Cite
|
Sign up to set email alerts
|

Associations between the use of herbal medicines and adverse pregnancy outcomes in rural Malawi: a secondary analysis of randomised controlled trial data

Abstract: BackgroundThe use of herbal medicines during pregnancy is very high globally and previous studies have pointed out possible associations with adverse pregnancy outcomes. Nevertheless, the safety of herbal medicines in pregnancy is under-explored in low-income countries experiencing high maternal and neonatal complications. We investigated the associations between self-reported use of Mwanamphepo (a group of herbal medicines commonly used to induce or hasten labour) and adverse maternal and neonatal outcomes in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
33
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(41 citation statements)
references
References 40 publications
7
33
0
1
Order By: Relevance
“…Fourteen interventional 5669 and 11 observational studies 34,7079 were graded as high quality; 10 interventional 8089 and 13 observational studies 14,31,90100 were graded average quality, and five interventional 101–105 and two observational studies 24,106 were graded poor quality. These poor-quality studies were still included in the review, only low-quality case reports were excluded (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Fourteen interventional 5669 and 11 observational studies 34,7079 were graded as high quality; 10 interventional 8089 and 13 observational studies 14,31,90100 were graded average quality, and five interventional 101–105 and two observational studies 24,106 were graded poor quality. These poor-quality studies were still included in the review, only low-quality case reports were excluded (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Excluding case reports, specific safety concerns, such as adverse drug reactions, congenital malformations, fetal growth restriction and herb–drug interactions, were the primary study objective reported by 19 studies, 16 cohort studies, 31,34,7075,7779,92,95,96,98,100 one cross-sectional survey, 76 and two randomized controlled trials. 64,68…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…When used at a high dose, it may cause excessive uterine stimulation leading to adverse reactions. The adverse effects linked to "Isihlambezo" formulation include low neonatal birth-weights, fetal meconium staining, which was a sign of possible fetal distress and hypoxia, and fatal uterine rupture (Veale et al, 1998 (Zamawe et al, 2018). In Korea, the herbal formulation "Anjeonicheon-tang" containing Atractylodes macrocephala Koidzumi white rhizoma, Glycyrrhiza glabra L. rhizoma, Panax ginseng C.A.Mey.…”
Section: Consumption Of Hms By Pregnant Womenmentioning
confidence: 99%
“…In rural Malawi for instance, the odds of maternal morbidity were 28% higher among self-reported users than non-users of a popular herb, mwanamphepo. Furthermore, the probabilities of neonatal morbidity or death were 22% higher among neonates whose mothers reported use of the mwanamphepo than those who did not [28]. Signi cantly higher odds of having postnatal complications have also been observed among women in Tanzania who reported use of local herbs during pregnancy or delivery versus those who did not [18].…”
Section: Discussionmentioning
confidence: 99%